A REVISION OF MALESIAN GIGANTOCHLOA (POACEAE - BAMBUSOIDEAE) - widjaja, Elizabeth A. (REINWARDTIA, 1987)
Eighteen species of Gigantochloa are recognized from the Malesian area, of which ten species are wild and the rest are known only in cultivation. Besides morphological and anatomical evidences, data derived from chemotaxonomical analyses are also utilized in the systematic study of these species. A new combination (G. pseudoarundinacea) and four new species (G. achmadii, G. atroviolacea, G. manggong and G. pruriens) are proposed. Moreover a doubtful species (G. heteroclada) is also mentioned. Full illustrated descriptions, complete list of synonymy and typification aa well as sundry notes for each species treated are presented. Keys to all species and varieties recognized (based on the inflorescence and vegetative characters) are given and an index of all specimens examined is also appended.